2018
DOI: 10.3390/en11082019
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Continuance Usage of Natural Gas: A Theoretical Model and Empirical Evaluation

Abstract: The adoption of natural gas increased notably last years, and there is some recognition that it improves the quality of life of inhabitants. While initial acceptance is an essential first step, the continued use is relevant to the long-term success of any technology. However, the literature on energy has focused on adoption and has devoted less attention to models that explain continuance usage. Accordingly, this study developed a model to explain continuance usage, grounded in Expectation-Confirmation Model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…We can find certain examples in the literature where the price value construct has been studied as a predictor of users continuance intentions (Fernández-Guzmán & Bravo, 2018;Tam et al, 2020). For example, Tam et al (2020) used ECM framework to investigate the critical factors that influence the continuance intention to use mobile apps, and they confirmed that the effect of price value on continuance intention is not significant.…”
Section: Moderating Variablesmentioning
confidence: 97%
See 1 more Smart Citation
“…We can find certain examples in the literature where the price value construct has been studied as a predictor of users continuance intentions (Fernández-Guzmán & Bravo, 2018;Tam et al, 2020). For example, Tam et al (2020) used ECM framework to investigate the critical factors that influence the continuance intention to use mobile apps, and they confirmed that the effect of price value on continuance intention is not significant.…”
Section: Moderating Variablesmentioning
confidence: 97%
“…Prior research provides some evidence for environmental concerns/consciousness in relation to a user's decision for environmentally friendly products (Belanche et al, 2012;Fernández-Guzmán & Bravo, 2018). Fernández-Guzmán and Bravo (2018) used ECM framework to study the continuous usage of natural gas, and they confirmed significant effects of environmental consciousness on the Intention of Continued Use.…”
Section: Moderating Variablesmentioning
confidence: 98%
“…Compared to objective indicators, beliefs play a rather direct role in the decision of adoption [14]. Renowned adoption theories (e.g., the theory of reasoned action, the theory of planned behavior, value belief and norm theory, and technology acceptance model) focus on human behavior components and are widely used in literature for a diverse range of technologies, including renewable energies [19,[25][26][27][28][29][30][31][32]. These theories highlight the behavioral factors' subjective beliefs and norms, perceived usefulness, perceived ease to use, attitude, and intentions as important for making decisions to adopt technologies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Second, we also consider the post-adoption beliefs of the households, as these beliefs are crucial for the continuation of the technology in the long-term because the overall success of new technology can only be observed if it is fully diffused. Adoption is considered the initial step in the acceptance of any technology, but the true diffusion and actual success of the technology depend on its continued use [19]. The ineffective and irregular use of technology in the long-term often leads to failure of that technology, and one cannot classify such technology as a success [12].…”
Section: Introductionmentioning
confidence: 99%
“…In sum, this research adopts a longitudinal survey because perceived usefulness, perceived pleasure, perceived arousal, attitudes toward information technology, and continuance intention are all regarded as trait variables (e.g., persistent personality variables) [ 20 , 21 , 22 ]. Additionally, the previous study on continuance intention was almost just cross-sectional samples [ 23 , 24 , 25 ], so there is currently little evidence of the causal relationship between continuance intention and its antecedent. By using the LGCM, this research can fill these literature gaps in the information technology field.…”
Section: Introductionmentioning
confidence: 99%